2007
DOI: 10.1007/s11244-007-0198-7
|View full text |Cite
|
Sign up to set email alerts
|

Promotion effect of surface Lanthanum in soot oxidation over ceria-based catalysts

Abstract: In the present work the soot combustion activity of CeO 2 doped with lanthanum hydroxide, as surface promoter, has been investigated. TGA experiments, run under different conditions, show that, in the presence of lanthana, the reaction of soot starts at low temperature (579 K) due to the possibility to form carbonate species. The emission of CO 2 is delayed due to the strong interaction with lanthana. A mechanism of reaction involving a carbonate route is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This was likely the case in this study, because of the low catalyst surface area of CeO 2 (∼2 m 2 g –1 ); therefore, the dramatic increase in activity after lanthanum doping may be related to both physical and chemical changes in the catalyst. The lanthanum on the surface of CeO 2 could also improve the soot oxidation activity by introduction of a carbonate pathway . Katta et al compared zirconium- and lanthanum-doped ceria solid solutions for soot oxidation and found that lanthanum-doped ceria solid solutions (Ce/La = 2/1, Δ T 50 = 165 °C) gave much higher activity than the zirconium-doped ceria solid solutions (Ce/Zr = 1, Δ T 50 = 110 °C) and undoped ceria (Δ T 50 = 30 °C).…”
Section: Oxidation Of Carbonaceous Depositsmentioning
confidence: 99%
“…This was likely the case in this study, because of the low catalyst surface area of CeO 2 (∼2 m 2 g –1 ); therefore, the dramatic increase in activity after lanthanum doping may be related to both physical and chemical changes in the catalyst. The lanthanum on the surface of CeO 2 could also improve the soot oxidation activity by introduction of a carbonate pathway . Katta et al compared zirconium- and lanthanum-doped ceria solid solutions for soot oxidation and found that lanthanum-doped ceria solid solutions (Ce/La = 2/1, Δ T 50 = 165 °C) gave much higher activity than the zirconium-doped ceria solid solutions (Ce/Zr = 1, Δ T 50 = 110 °C) and undoped ceria (Δ T 50 = 30 °C).…”
Section: Oxidation Of Carbonaceous Depositsmentioning
confidence: 99%
“…The reason for the catalytic effect is oxygen donation of CeO 2 caused by partial Ce 4+ /Ce 3+ reduction on the surface of catalyst particles [3]. This effect can be further increased, using CeO 2 -ZrO 2 solid solutions and compounds or doping with transition and rare-earth metals [4][5][6][7]. Ceria can be used as a water-gas shift catalyst in combination with precious transition metals [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, several transition metal oxides, including Ce, Co, Mn, Fe, Cu, V, and Mo [6][7][8][9][10][11][12][13][14][15], have been demonstrated as catalysts to decompose soot. Ce, especially CeO 2 , has become a particularly attractive catalyst for soot oxidation as CeO 2 exhibits a relatively high oxygen storage capacity via the redox cycle between Ce 4+ and Ce 3+ for reversibly adding/removing oxygen, making CeO 2 possess high catalytic activities [1,16].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, catalytic decomposition of soot has been regarded as a key step for eliminating soot [2][3][4][5], and catalysts for soot oxidation at lower temperatures and higher reaction rates are then highly crucial [2]. Up to date, several transition metal oxides, including Ce, Co, Mn, Fe, Cu, V, and Mo [6][7][8][9][10][11][12][13][14][15], have been demonstrated as catalysts to decompose soot. Ce, especially CeO2, has become a particularly attractive catalyst for soot oxidation as CeO2 exhibits a relatively high oxygen storage capacity via the redox cycle between Ce 4+ and Ce 3+ for reversibly adding/removing oxygen, making CeO2 possess high catalytic activities [1,16].…”
Section: Introductionmentioning
confidence: 99%